Self-Calibration of the Resolver Sensor in Servo Drive Application - Faber, Jan; Stulrajter, Marek; Vittek, Jan (Communications - Scientific letters of the University of Zilina, 2013)
Resolver sensor is utilized as absolute position transducer in many industrial motion-control applications where robustness and ability to operate in harsh environment is required. In real system, the quality of position and speed measurement is badly affected by the resolver errors. In this paper, the software-based error-compensation technique is integrated into the control structure of the drive. Compensation scheme adapts online to errors in the resolver signals in order to improve accuracy of the measured position and speed. Performance of the compensation scheme and the effect on the drive operation is verified through experimental testing.